2014
DOI: 10.1016/j.anndiagpath.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of notch signaling pathway in salivary adenoid cystic carcinoma

Abstract: Background Notch signaling plays role in stem cell biology, tumor formation, angiogenesis, and cell death. Targeting Notch pathway could serve as a therapeutic strategy in cancer. Little is known about the differential role of various components of the Notch pathway in salivary AdCC. Methods To investigate the association of the Notch pathway in AdCC carcinogenesis, we analyzed the Notch receptors (Notch-1, Notch-2, Notch-4) and Notch ligands (Jagged-1, Delta) expressions. Results The results showed elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…Given these findings, it is possible that FABP7 expression is regulated by the Notch signaling pathway in ACC. These results are intriguing in light of another study showing that NOTCH1 immunostaining was similar to what we observed here for FABP7 [39] . If this is the case, FABP7 may be a useful biomarker to measure response to Notch inhibitors in salivary tumors.…”
Section: Discussionsupporting
confidence: 90%
“…Given these findings, it is possible that FABP7 expression is regulated by the Notch signaling pathway in ACC. These results are intriguing in light of another study showing that NOTCH1 immunostaining was similar to what we observed here for FABP7 [39] . If this is the case, FABP7 may be a useful biomarker to measure response to Notch inhibitors in salivary tumors.…”
Section: Discussionsupporting
confidence: 90%
“…mRNA profiling indicated the overexpression of several genes within the PI3K, MAPK, Wnt, and Notch pathways. Specifically, our screen detected several genes known to be overexpressed or mutated in ACC, including MYB, P53, and NOTCH1 (46). Many of the genes detected as overexpressed in our samples (i.e., FGFR1, JAG1, and expressing checkpoint receptors Lag-3, Tim-3, and PD-1 over the course of chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of mutations were unique or only in a small fraction of the tumors, the altered genes could be grouped together by their potential to disrupt specific cellular functions or biochemical pathways. This included those that interact with the MYB transcription network, but also genes that influence chromatin remodeling, DNA damage/checkpoint responses, signaling pathways regulated by fibroblast growth factor (FGF)‐insulin‐like growth factor‐PI3K, protein kinase A pathway, or Notch 24, 25, 35, 36. Understanding the specific contribution of each mutation to tumorigenesis might lead to novel pathways for targeted therapy.…”
Section: Introductionmentioning
confidence: 99%